Production and characterization of PHA from recombinant E. coli harbouring phaC1 gene of indigenous Pseudomonas sp. LDC-5 using molasses - Saranya,V (2011)
Polyhydroxyalkanoates (PHA) are biodegradable and biocompatible green thermoplastics, synthesized by wide variety of bacteria as an intracellular carbon and energy storage intermediate. They are used as an alternative to nonrenewable petroleum derived plastics. The current interest in these biopolyesters is stimulated by the search for cost-effective capitalized production. This paper attempts to achieve maximized production rate from recombinant system using inexpensive substrate. Molasses from agro-industrial waste was used to produce PHA from recombinant E.coli in batch culture. PHA yield in molasses (3.06g/L ± 0.05-75.5%) was higher than that of sucrose (2.5g/L ± 0.05 - 65.1%). Properties of the polymer produced from molasses and sucrose were analyzed by DSC, TGA, DTA, GC/MS, TLC and optical rotation studies. The findings suggested that molasses enhanced PHA production in recombinant E.coli.